Overview on the modelling of the biomechanical behavior of the intervertebral disc - Castro, André
The present work draws an overview on the numerical modeling and numerical simulation of the biomechanical behavior of the Intervertebral Discs (IVD). Since 1974 that several research groups around the world have been devoting attention to this subject and several examples of the application of the Finite Element Analysis (FEA) to study the biomechanics of the IVD can be found. The authors of the present work are presently working under the scope of a wider European project which main expected achievements are: 1) to investigate the biomechanisms of disc degeneration; 2) to develop a biomimetic strategy for the IVD regeneration; 3) the development of several numerical tools, with a special emphasis on a spine-oriented FEA solver, in order to contribute to the investigation of new strategies for treatment and/or rehabilitation of the Degenerative Disc Diseases. The presented overview aims to establish the starting point of such research work.